Christian Nationalism in the United States - Mark T. Edwards (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The essays in this collection engage and build upon the exciting new scholarship in the histories of Christian nationalism within the United States. They cover topics ranging from the Native American preacher William Appess, Federalist party leaders, Manifest Destiny, and West Point, to Donald Trump, the evangelical thinker Richard Mouw, the ecumenical movement, evangelical internationalism, and religious pluralism. Taken together, the contributors discard the old question of whether or not America was ever a Christian nation. Instead, they are concerned with how and why certain persons and groups throughout American history have either embraced or rejected the myth of a religious founding as a political project.